2004
DOI: 10.1101/gad.1168104
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of TAK1 by the NF-κB protein Relish regulates the JNK-mediated immune response in Drosophila

Abstract: The molecular circuitry underlying innate immunity is constructed of multiple, evolutionarily conserved signaling modules with distinct regulatory targets. The MAP kinases and the IKK-NF-B molecules play important roles in the initiation of immune effector responses. We have found that the Drosophila NF-B protein Relish plays a crucial role in limiting the duration of JNK activation and output in response to Gram-negative infections. Relish activation is linked to proteasomal degradation of TAK1, the upstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
157
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(170 citation statements)
references
References 52 publications
10
157
1
2
Order By: Relevance
“…The biological consequences of the JNK pathway (DJNK) in Drosophila are less complicated than in mammals, functioning to preferentially promote apoptosis. Park et al 42 demonstrated that JNK activation is prolonged in S2 cells lacking Relish. Moreover, they showed that Relish activation leads to degradation of TAK1, resulting in termination of JNK signaling.…”
Section: Nf-jb Downregulates Jnkmentioning
confidence: 99%
“…The biological consequences of the JNK pathway (DJNK) in Drosophila are less complicated than in mammals, functioning to preferentially promote apoptosis. Park et al 42 demonstrated that JNK activation is prolonged in S2 cells lacking Relish. Moreover, they showed that Relish activation leads to degradation of TAK1, resulting in termination of JNK signaling.…”
Section: Nf-jb Downregulates Jnkmentioning
confidence: 99%
“…IKK has been shown to inhibit the transcription factor FOXO3a (Hu et al, 2004), which stimulates Bim gene transcription (Gilley et al, 2003;Sunters et al, 2003). Likewise, NF-B inhibits the effect of JNK on gene transcription (De Smaele et al, 2001;Tang et al, 2001;Park et al, 2004). JNK has been shown to control Bim transcription in cerebral ischemia (Kuan et al, 2003;Okuno et al, 2004).…”
Section: Mandola 2001mentioning
confidence: 99%
“…TAK, a MAPKKK, functions upstream of the IKK and downstream of IMD, a receptor interacting protein (De Gregorio et al, 2002;Lemaitre, 2004). In general, JNK and JAK/STAT pathway also could regulate AMPs (Garver et al, 2013;Park et al, 2004).…”
Section: Introductionmentioning
confidence: 99%